Beach Sand Filtrate as an Alternative Gas Fuel - Hasdinar Umar (Center of Techonolgy (COT), Engineering Faculty, Hasanuddin University, 2020)
The golden age of the oil business in Indonesia is over and now petroleum is even a burden. As oil producing countries prepare themselves to start the second phase of the golden era of oil, Indonesia is heading towards an era of energy crisis (Indirasardjana, 2014). Renewable energy is needed as an alternative to meet the community's fuel needs. Beach sand is one material that can be used to help the biomass gasification process. Small particles of sand are filled into a container and gas is flowed from below and suppresses the flow of each particle which is useful for the biomass decomposition process. When using beach sand, we can also utilize heat energy optimally in coastal areas to make gasification reactions easier. This study aims to examine the groups contained in the TMS (Tetramethylsilan) spectrum of the beach sand filtrate fluid by paying attention to the CH3 compounds which are arranged in TMS. FTIR test results show that the beach sand filtrate fluid gives an illustration that from wavelengths of 3000 to 3500 the sharpness of the amount of nitrogen and hydrogen in the sand beach filtrate liquid solution can be used as ammonia gas (a fuel). Nitrogen and Hydrogan when bound with Hydroxide will form ammonium hydroxide which can function as a fuel (heating).